De la multifonctionnalité des Coopératives d’activités et d’emploi : des modèles socioproductifs expérimentaux dans les zones grises de l’emploi et du travail - Justine Ballon (Revue de la Régulation)
In a context of changes in the organisation and mobilisation of work, the Business and Employment Cooperatives (BEC) establish mutualisation and cooperation forms between entrepreneur-salaried employees, the sustainability of which remains fragile. Creating a dialogue between the conceptual architecture of the regulation theory and the pragmatism of the social economy, this thesis revisits the productive models to qualify the cooperative government compromises of the BECs, by analysing their multifunctional productive dynamics. This research with scientific, pedagogical and operational aims lead to an original approach of integral participatory action research, an analysis grid, those of the socio-productive models of the BEC, an activity-based approach to work revealing a dual process of empowerment and democratisation, a reading of the complexity of the social relations of production with the cooperative relationship of activities and finally an exploratory definition of the multifunctionality of the BEC.